2007
DOI: 10.1371/journal.pone.0001039
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Surface Activity of a Fully Synthetic Phospholipase-Resistant Lipid/Peptide Lung Surfactant

Abstract: BackgroundThis study examines the surface activity and resistance to phospholipase degradation of a fully-synthetic lung surfactant containing a novel diether phosphonolipid (DEPN-8) plus a 34 amino acid peptide (Mini-B) related to native surfactant protein (SP)-B. Activity studies used adsorption, pulsating bubble, and captive bubble methods to assess a range of surface behaviors, supplemented by molecular studies using Fourier transform infrared (FTIR) spectroscopy, circular dichroism (CD), and plasmon reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 60 publications
4
33
0
Order By: Relevance
“…In addition, several synthetic exogenous surfactants are under clinical study and laboratory research. [16][17][18][19][20][21][22][23][24] …”
Section: A Brief Historymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several synthetic exogenous surfactants are under clinical study and laboratory research. [16][17][18][19][20][21][22][23][24] …”
Section: A Brief Historymentioning
confidence: 99%
“…One particularly active synthetic lipid analog of this kind is DEPN-8, a phospholipase-resistant diether lipid developed by Notter and co-workers. 19,21,23,46,47 Synthetic surfactants containing DEPN-8 or other phospholipase-resistant lipids plus active SP-B peptides have the potential for particular utility in ALI/ ARDS, 19,21,23,[48][49][50] where these lytic enzymes can be elaborated in high concentrations during the inflammatory response in injured lungs. [51][52][53][54][55][56][57] Regardless of category (animal-derived or synthetic), the requirements for an effective therapeutic surfactant in ALI/ARDS are more stringent than is the case for RDS.…”
Section: Pharmaceutical Surfactantsmentioning
confidence: 99%
“…Phospholipase-induced degradation of lung surfactant glycerophospholipids not only reduces the concentration of active components, but also generates reaction products such as lysophosphatidylcholine and fluid free fatty acids that can further decrease surface activity by interacting biophysically with remaining surfactant at the alveolar interface [55,59,70]. Synthetic exogenous surfactants containing such phosphonolipids combined with purified surfactant proteins or synthetic peptides have very high overall surface activity plus an ability to resist phospholipases in ALI/ARDS [71,[208][209][210][211]219]. On-going basic research is continuing to design and synthesize peptides related to SP-B and other surfactant proteins for use in highly-active fully-synthetic exogenous surfactants in combination with either normal glycerophospholipids or phospholipase-resistant analogs.…”
Section: Examples Of Research On New Synthetic Exogenous Surfactamentioning
confidence: 99%
“…Based on the anti-inflammatory effects of HA and its ability to reduce PLA 2 activity, and thus minimize surfactant inhibition, it has been suggested that concomitant treatment with HA and surfactant might provide a promising approach to the treatment of ARDS. An alternative approach, described in recent papers, has focused on the use of PLA 2 -resistant surface-active phosphonolipids to develop new artificial surfactants (49,66,67), which may eventually prove to have advantages in the treatment of ARDS.…”
Section: Discussionmentioning
confidence: 99%